Multidisciplinary effort in treating children with hepatoblastoma in China. Issue 1 (28th May 2016) - Yuan, Xiao-Jun; Wang, Huan-Min; Jiang, Hui; Tang, Meng-Jie; Li, Zhang-Lin; Zou, Xiang; Fang, Yong-Jun; Pan, Ci; Tou, Jin-Fa; Zhang, Ke-Ren; Liu, Xiang; Li, Wei-Song; et al.
Highlights: Pediatric patients with HB in China have had similar OS and EFS rates in recent years compared to developed countries. Wuhan Protocol is the first national guideline developed by Chinese Children's Cancer Group. The protocol was proved to be feasible and effective in China. Standardization of surgical resection and risk-based chemotherapy should be further optimized for pediatric HB patients. Abstract: The purpose of this study is to report the first nationwide protocol ( Wuhan Protocol ) developed by Chinese Children's Cancer Group and the results of multidisciplinary effort in treating hepatoblastoma. In this study, we reported the final analysis, which includes 153 hepatoblastoma patients in 13 hospitals from January 2006 to December 2013. The 6-year overall survival and event-free survival rates were 83.3 ± 3.1% and 71.0 ± 3.7%, respectively, in this cohort. The univariate analysis revealed that female ( P = 0.027), under 5 years of age ( P = 0.039), complete surgical resection ( P = 0.000), no metastases ( P = 0.000), and delayed surgery following neoadjuvant chemotherapy ( P = 0.000) had better prognosis. In multivariate analysis, male, 5 years of age or above, stage PRETEXT III or IV, and incomplete surgical resection were among the some adverse factors contributing to poor prognosis. The preliminary results from this study showed that patients who underwent treatment following Wuhan Protocol had similar OS and EFS rates compared to those in developed countries. However, the protocol remains to be further optimized in standardizing surgical resection (including liver transplantation), refining risk stratification and risk-based chemotherapy.